Gingival Recession Management A Clinical Manual (Springer International Publishing, 2018)
This book is designed to serve as a clear and concise clinical manual that covers all aspects of the current management of gingival recession, with a particular focus on surgical techniques with the adjunctive use of autogenous tissues or soft tissue substitutes for recession coverage. A structured overview of the various surgical techniques is provided with the aid of high-quality illustrations, delivering an evidence-based clinical treatment guideline. In addition, individual chapters are dedicated to the classification of gingival recession, etiology and prevalence, clinical examination and diagnosis, decision making, potential complications, and postsurgical care. Gingival recession is a common condition in the adult population and is related to several undesirable conditions such as unaesthetic appearance, root caries, and hypersensitivity. Periodontal plastic surgery is now an important tool in the armamentarium of the clinician treating gingival recessions, and practitioners at all levels will find this book to be an invaluable source of guidance.